Effective learning and teaching in social policy and social work - Burgess, Hilary, 1954-; Taylor, Imogen (RoutledgeFalmer, 2005)
Written to meet the needs of teachers, lecturers and tutors working at different levels and in many situations, this is the guide to understanding the key issues, best practices and new developments in social work and social policy.
Keywords: Social policy -- Study and teaching (Higher); Human services -- Study and teaching (Higher); Social work education.; Service social -- Étude et enseignement.; POLITICAL SCIENCE -- Public Policy -- Social Policy.; Social work education